Unveiling the mechanisms for microtubule-based peroxisome motility and distribution by exploiting the filamentous fungus U. maydis - Guimarães, Ana Sofia da Cunha (2016)
Peroxisomes are ubiquitous subcellular organelles, which fulfil important metabolic functions, notably the β-oxidation of fatty acids and the metabolism of hydrogen peroxide, and are thus essential for human health and development. The filamentous fungus Ustilago maydis is a biotrophic, basidiomycete responsible for corn smut disease. U. maydis exhibits several features similar to mammals including polar growth, microtubule-dependent organelle trafficking and open mitosis. In this study, we have exploited U. maydis as a new model system for studying fundamental processes in peroxisome biology. An intimate interrelationship between peroxisomes and mitochondria is emerging, where both organelles cooperate in cellular lipid homeostasis, oxidative balance, and innate immune response. As mitochondrial fatty acid β-oxidation is lacking in yeast and plants, suitable genetically accessible model systems to study this interrelationship are scarce. Combined molecular, cell biology and bioinformatics analyses were performed to provide a first comprehensive inventory of U. maydis peroxisomal proteins and pathways. Studies with a peroxisome-deficient Δpex3 mutant revealed the existence of parallel and complex, cooperative β-oxidation pathways in peroxisomes and mitochondria, mimicking the mammalian system. In mammalian cells, peroxisomes bind to and move along microtubules. In contrast, peroxisome motility in yeasts and plants requires the actin cytoskeleton. Peroxisome motility and dynamics are important prerequisites for peroxisome inheritance, proper intracellular distribution, positioning, organelle interactions, and biogenesis. A loss of trafficking and disturbed cytoplasmic distribution of peroxisomes can lead to a regional loss of essential peroxisomal activities and thus, to cell damage and degeneration. We revealed that peroxisomes in U. maydis move along microtubules, but peroxisome motility is early endosome-dependent. Moreover, lipid droplets and the ER appear to share a similar mechanism. Even distribution of peroxisomes is critical for cellular functions. However, the exact mechanism(s) for uniform peroxisome distribution are elusive. Using U. maydis, we demonstrated that the distribution and positioning of peroxisomes is dependent on microtubule-based processes and an actin-based polar drift. Microtubule-based processes include directed transport and active diffusion, which is a result of a constant flow and activity of motor proteins and organelles. These counteracting forces allow the proper distribution of peroxisomes throughout the hyphal cell. Moreover, work in mammalian cells, revealed a similar mechanism for proper distribution of peroxisomes. In summary, we provide novel evidence that the filamentous fungus U. maydis represents a suitable model to study fundamental biological processes of mammalian cells. Peroxisome motility and dynamics are important for cellular function and may prevent cell damage and degeneration. The use of U. maydis as a model system will lead to a better understanding of peroxisome dynamics and biology and will thus be of great cell biological and biomedical importance.